The Chiasmus of Mourning and Identification in Jean Genet - Peter Benson (Studies in 20th & 21st Century Literature, 2000)
The theories of psychological identification proposed by Sigmund Freud and Kaja Silverman are explored in relation to Jean Genet's Funeral Rites and his later essay on Rembrandt. Genet can be seen to separate mourning (which for Freud lies at the basis of identification) from a process of generalized identification in which his difference from other people dissolves. A narcissistic formation of personality, evident in the symbolism of mirrors in Funeral Rites, gives to this process an added impetus. But the fundamental condition of possibility for such generalized identification is the void it reveals at the center of all personality. This void not only makes possible the different kinds of identification (heteropathic and idiopathic) described by Silverman, it also disturbs any clear distinction between them. It is for these reasons that the glamorization of Nazism in Funeral Rites is coextensive with a demystification of its power, and the often brutal eroticism of the book is suffused with an ineradicable dimension of tenderness. Taken further in the essay on Rembrandt, these themes lead to an ambiguous mysticism in which the source of creativity is revealed as inseparable from its ultimate obliteration.
Keywords: Jean Genet; psychology; psychological identification; Freud; Kaja Silverman; Funeral Rites; Rembrandt; mourning; identification; narcissism; personality; Nazism; mysticism